Spy x family. 9 - Endō, Tatsuya, 1980- (VIZ Media, LLC, 2023)
Master spy Twilight is unparalleled when it comes to going undercover on dangerous missions for the betterment of the world. But when he receives the ultimate assignment--to get married and have a kid--he may finally be in over his head! Yor's on assignment and finds herself up against a gang of assassins on board a luxury cruiser. Meanwhile, Loid and Anya each discover that bombs have been planted throughout the ship! Will their best efforts be enough to save the vessel?